The Intersection of Philippine and Global Film Cultures in the New Urban Realist Film - Campos, Patrick F. (Plaridel Journal of Communication, Media, and Society, 2011)
With the rise of indie cinema in the Philippines, many say that another golden age is again in the making, and, like its predecessor, the films are being produced in the midst of widespread poverty and political instability. Understandably, a significant number of indie films has consciously returned to and explored the limits of the urban realist film of the 'golden age' (1975-1984), revisioning city spaces and signifying patterns in Philippine and global film cultures. The essay has three intricately connected sections. On the one hand, it delineates the shifting contexts of Philippine and global film cultures and situates current indie cinema in these contects. On the other hand, by considering several key films, it traces the development and revisions of urban realism from its birth until today and reflexively problematizes the critical discourses that define and are defined by such realism. Keywords: Philippine cinema, realism, city studies, film culture